Economic implication of Moslem pilgrimage from Malaysia - Din, Abdul Kadir (ISEAS, 1982)
The conduct of the hajj, or pilgrimage to Mecca, has been the subject of considerable interest among orientalists since the time of the early travellers in the thirteenth century. Their writings on the subject, mainly in the form of travel accounts and personal diaries, have tended to describe in detail the mysteries surrounding the exclusiveness of Mecca and the legendary novelties experienced during the sacred journey. Little attempt was made to study the economic aspects of the institution although of late there have been some efforts in this direction. These latter works have considered the hajj as a form of tourism and consequently, in line with the recent tradition in touristic studies, have tended to emphasize the socio-economic impacts of the hajj on the destination area (Turner 1973; Graburn 1977; Cohen 1979; Long 1979). In this paper it is argued that it would be less than realistic to treat hajj as a form of tourism, for in doing so one may over-emphasize its Impact on the destination areas. This paper the examines the implications of Malay pilgrimage from Malaysia and subsequently makes some preliminary remarks on the role of the nascent Muslim Pilgrimage Control and Savings Corporation in the economic betterment of the Malays.